Pengaruh Content Marketing, E-Wom Dan Customer Trust Terhadap Keputusan Pembelian Gen-Z Pada Smartphone Samsung - Muhammad Daffa Fauzan; Agus David Ramdansyah; Yanto Azie Setya (Sains: Jurnal Manajemen dan Bisnis, 2025)
This study aims to analyze the effect of content marketing and electronic word of mouth (e WOM) on purchasing decisions with customer trust as a mediating variable, especially for Generation Z Samsung smartphone users in Tangerang City. The background of this study is based on the decline in Samsung's sales and market share in the last five years, as well as the high dependence of Gen-Z consumers on digital media and online reviews in making purchasing decisions. The method used is quantitative with a Structural Equation Modeling (SEM) approach using SmartPLS 4.0 software. Data was obtained through distributing questionnaires to 170 Gen-Z respondents who use Samsung smartphones. The results showed that content marketing and e-WOM have a positive and significant effect on purchasing decisions, both directly and indirectly through customer trust as a mediating variable. This finding confirms that consumer trust plays a crucial role in strengthening the effectiveness of digital marketing strategies. This research is expected to contribute to the development of digital marketing literature and become a strategic reference for industry players in developing effective marketing campaigns that are oriented towards customer trust.